The contribution of services to development and the role of trade liberalisation and regulation - Cali, Massimiliano (Overseas Development Institute LondonGB, 2008)
Seeks to understand how trade liberalization can be made to work. Discusses the role of regulation and regulation reform in the development of service sectors. Examines how liberalisation and regulation affect development at the level of the sector and to consider capacity issues as complementary factors.